Kierkegaard in the Garden: The Interiority of God’s Wonder and Praise - Moon, Catherine (Lumen et Vita, 2017)
Is there an interior aesthetic? Can each and every human being turn inward and behold a beauty and nobility that leads them to the face of God? Or are aesthetics a purely outward manifestation of the beauty and order that points to the ultimate Creator? In this essay, I plan to expound on how God in all His grace and love might have made himself known in His essence to the whole of humanity in the most intimate way not simply by the more objective, sterile mode of reason, but by the subjective passionate mode of beauty. First, I will look at Genesis 1:10 in the Greek of the Septuagint, “καὶ εἶδεν ὁ Θεός, ὅτι καλόν” as a manner of demonstrating that God marveled at Creation, before he created the first human being. He took the time to perceive its beauty and nobility. Through this I plan to look at the relationship between wonder and beauty and how the interplay of those two yields truth. When God saw that His Creation was good was that an interior aesthetic of His own or a mediation of Himself? To sort this out, I plan to look at Soren Kierkegaard in his Concluding Unscientific Postscript to show that interiority and the subjective do possess and partake in the kind of possession that allows one not only to see God or His attributes, but enables one to abide in Him through the Spirit.